2015
DOI: 10.5539/jas.v7n5p47
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Temperate Selected Sesame Accessions in the Tropics: Selected for Japan and Grown in Ghana

Abstract: Sesame is an oilseed crop which can be grown on marginal lands. Selection of stable sesame cultivars that can adapt to local environmental conditions can be a very important food security strategy. A set of 21 high yielding sesame accessions that have been selected for a temperate region were grown in the transitional zone of Ghana during the major season of 2014. The seeds were sown after the first rain in the year in a completely randomized design, with three replications. The objective was to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…These results were expected, because of the highly significant correlations among the three traits (PH, LFZ, and SYP −1 ) in the base populations. These results agree with those reported by [20,24,25], who indicated that yield improvement would be possible via selection for number of number of capsules plant −1 , diameter of stem, capsule length, number of branches per plant, and plant height.…”
Section: Correlations Among Traits In the Base Populations (F2-genera...supporting
confidence: 92%
See 1 more Smart Citation
“…These results were expected, because of the highly significant correlations among the three traits (PH, LFZ, and SYP −1 ) in the base populations. These results agree with those reported by [20,24,25], who indicated that yield improvement would be possible via selection for number of number of capsules plant −1 , diameter of stem, capsule length, number of branches per plant, and plant height.…”
Section: Correlations Among Traits In the Base Populations (F2-genera...supporting
confidence: 92%
“…Two cycles of pedigree selection started in the F 2 decreased genotypic and phenotypic variations, significantly lowered height to first capsule, and increased the observed genetic gains of plant height, as well as the number of capsules plant −1 (43.21% and 81.52%) and seed yield in two populations (30.68% and 45.18% of the better parent) [21]. Number of capsules plant −1 and 1000 seed weight could be used as selection criteria to increase seed yield [17,[22][23][24]. This work aimed to improve seed yield, tolerance, and/or resistance to F. oxysporum through selection of eight criteria; earliness, plant height, height to the first capsule, length of fruiting zone, and seed yield; with earliness, plant height, and length of fruiting zone restricted by seed yield, under artificial infection of F. oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual increase in temperature and day length hours enhanced stem diameter both in case of planting intervals and sesame varieties. These results corroborate the findings of Malik et al (2003); Fazli et al (2010); Saleem et al (2008); Ehsanullah et al (2007); Ansah (2015); Blal et al (2012) and Ravusaheb et al (2010), who also reported similar effects on stem diameter. The interaction among the sowing dates and sesame varieties was found to be non-significant, as shown in Table 7.…”
Section: Stem Diametersupporting
confidence: 90%
“…Slowly but surely, increasing temperature and photoperiod enhanced seed weight (t ha -1 ), and sesame sowing dates and varieties are also paly a significant role.. These findings are in agreement with Noorka et al (2011); Ansah (2015) & Blal et al (2012. The interaction among the sowing dates and sesame varieties was found to be non-significant, as shown in Table 5.…”
Section: Seed Weight T Ha -1supporting
confidence: 87%
See 1 more Smart Citation